Paradoxical Air Embolus During Endoscopic Retrograde Cholangiopancreatography: An Uncommon Fatal Complication. (1st April 2015) - Markin, Nicholas W.; Montzingo, Candice R.
Abstract : Air embolism during endoscopic retrograde cholangiopancreatography is a rare but potentially fatal complication. A 66-year-old man underwent endoscopic retrograde cholangiopancreatography and remained stable until the end of the procedure, when he was found to have mottling on his right side and became hypoxic and unresponsive. Transesophageal echocardiography showed air within the left ventricle, consistent with systemic air embolism. Mortality resulted from significant cardiac and cerebral ischemia. The literature suggests that capnography is helpful in early diagnosis of air embolus, but it could not be used in this case because the patient's trachea was not intubated. Abstract : Supplemental Digital Content is available in the text.